LEGAL PROTECTION OF DIGITAL COPYRIGHT IN THE SOCIAL MEDIA ERA (CASE STUDY OF INDRA LESMANA'S MUSIC LABEL DISPUTE) - Fadhilatul Fitriya, Armaya; Indrawati, Septi; Alfian, Muh. (Pena Cendekia Insani, 2025)
This study aims to analyze the legal protection of digital copyrighted works in the social media era, focusing on a case study of the dispute between musician Indra Lesmana and a music label. Using a normative juridical approach and a case study method, this study examines the legal provisions of Law Number 28 of 2014 concerning Copyright and its implementation in the context of digital distribution through platforms such as YouTube and streaming services. The results of the study indicate that although the moral and economic rights of creators have been clearly regulated in regulations, digital distribution practices still leave room for violations, primarily due to outdated licensing contracts that are not adaptive to technological developments. The Indra Lesmana dispute is a concrete example of the weak bargaining position of creators, when labels use digital systems such as Content ID and DRM to claim exclusive rights to copyrighted works. This study concludes that legal protection in the digital realm is not yet fully effective and that contract reformulation and more responsive dispute resolution mechanisms are needed to ensure that creators' rights remain protected amidst the massive expansion of digital distribution.